Applications of computing and communication technologies : first International Conference, ICACCT 2018, Delhi, India, March 9, 2018, Revised selected papers /: first International Conference, ICACCT 2018, Delhi, India, March 9, 2018, Revised selected papers. (2018) - Unknown
No abstract available